English Speaking Skill through Rosetta Stone Application at Junior High School: Students’ Voices - Anisah Firly Chaniago; Benni Ichsanda Rahman HZ (South Sulawesi Education Development (SSED), 2024)
This study aims to explore the impact of utilizing the Rosetta stone application as a means to improve English speaking skills among second-grade junior high school students. The study employs a qualitative case study approach and data content analysis to delve deeply into the experiences and perceptions of the students regarding their English-speaking skill development through the application. Using a modified questionnaire and depth interviews, the researcher collected data through share the questionnaires to 34 students and interviews conducted with three participants. The results reveal that the majority of students express positive perceptions about the application's impact on English speaking abilities, citing improvements in confidence, vocabulary, accent, and overall learning experience. Overall, these findings underline the dynamic nature of language learning and the potential for continuous improvement in educational technology through targeted enhancements and further empirical exploration. These findings underscore the effectiveness of integrating technology like Rosetta Stone in language learning environments, offering diverse speaking practice opportunities, immersive learning experiences, and targeted feedback that contribute to overall language proficiency. The findings of this study could be useful for language learners who are seeking to improve their language skills as well as for educators and developers who are interested in creating effective language learning tools.